2004
DOI: 10.1007/s00535-003-1363-9
|View full text |Cite
|
Sign up to set email alerts
|

Factors contributing to ribavirin dose reduction due to anemia during interferon alfa2b and ribavirin combination therapy for chronic hepatitis C

Abstract: Because patient age of 55 years or more, and Hb levels of less than 14 g/dl are significant factors that influence ribavirin-induced hemolytic anemia, more careful monitoring is necessary during combination therapy for patients with these risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
68
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(77 citation statements)
references
References 24 publications
7
68
2
Order By: Relevance
“…(16)(17)(18) Historically, age has been a major limitation of antiviral treatment with interferon-based therapy because of its poor tolerability, adverse effects (AEs), and poorer response in older patients. (19)(20)(21)(22)(23)(24)(25) There is a lack of efficacy and safety information on HCV therapy in older patients, primarily due to underreporting and the exclusion of elderly subjects from clinical trials. (26,27) The combination of ledipasvir, an NS5A inhibitor, and sofosbuvir, a nucleotide polymerase inhibitor, has been approved by the US Food and Drug Administration, the European Medicines Agency, and in Japan as a fixed-dose combination tablet for the treatment of HCV genotype 1.…”
mentioning
confidence: 99%
“…(16)(17)(18) Historically, age has been a major limitation of antiviral treatment with interferon-based therapy because of its poor tolerability, adverse effects (AEs), and poorer response in older patients. (19)(20)(21)(22)(23)(24)(25) There is a lack of efficacy and safety information on HCV therapy in older patients, primarily due to underreporting and the exclusion of elderly subjects from clinical trials. (26,27) The combination of ledipasvir, an NS5A inhibitor, and sofosbuvir, a nucleotide polymerase inhibitor, has been approved by the US Food and Drug Administration, the European Medicines Agency, and in Japan as a fixed-dose combination tablet for the treatment of HCV genotype 1.…”
mentioning
confidence: 99%
“…Many previous studies reported that combination therapy with PEG-IFN and RBV for 24-48 weeks was effective in treating chronic hepatitis C (11). The most frequent toxic side effect of RBV is reversible hemolytic anemia, which requires some patients to reduce or discontinue combination therapy; the mechanism underlying hemolytic anemia involves the accumulation of RBV triphosphate in erythrocytes (12).…”
Section: Discussionmentioning
confidence: 99%
“…RBV-induced hemolytic anemia (HA) is usually reversible and dose related [115,116], but may require significant dose reductions possibly affecting efficacy, and is a cause of withdrawal from therapy in 10-14% of patients [64,[117][118][119][120]. Several risk factors for RBV-induced HA have been identified, for example, age, female gender, dose and plasma concentration of RBV, baseline hemoglobin and platelets, and haptoglobin phenotype [121][122][123][124]. However, the severity of RBV-induced HA shows great variability among individuals, suggesting that the genetic background may exert a profound influence on the clinical expression of this adverse effect.…”
Section: Molecular Epidemiology Of Hcv-relatedmentioning
confidence: 99%